Pengaruh Konseling Adiksi Berbasis Motivasi Terhadap Peningkatan Motivasi Untuk Pulih Pada Narapidana Kasus Penyalahgunaan Narkotika di Rutan Kelas IIB Majene - Muhammad Hafizh Khoiroot; Nurul Aeni; Fredy Akbar; Pattola Pattola (Yayasan Mandar Indonesia, 2026)
Drug abuse is a health problem that affects the physical, psychological, and social conditions of individuals. Low motivation to change becomes an obstacle in the recovery process of drug abusers; therefore, interventions that can increase individuals’ readiness to change are needed. Addiction counseling is one of the psychosocial interventions used to help improve motivation for change among drug abusers. This study aimed to determine the effect of addiction counseling on motivation for change among inmates with drug-related cases at Class IIB Majene Detention Center. This study used a pre-experimental design with a one-group pre-test post-test approach. The sample consisted of 15 respondents selected using purposive sampling based on the inclusion criteria, namely inmates with drug-related cases who were willing to participate as respondents, able to communicate well, and attended all addiction counseling sessions. Motivation for change was measured using the University of Rhode Island Change Assessment (URICA) questionnaire. Data were analyzed using the Paired t-test. The results showed that the mean score of motivation for change increased from 8.42 before the intervention to 10.97 after the addiction counseling intervention, with a p-value of 0.001 (p < 0.05). It can be concluded that addiction counseling has an effect on increasing motivation for change among inmates with drug-related cases at Class.